A 360° Rotational Positioning Protocol of Organ Donors May Increase Lungs Available for Transplantation*. Issue 8 (August 2019) - Mendez, Marissa A.; Fesmire, Alyssa J.; Johnson, Scott S.; Neel, Dustin R.; Markham, Lori E.; Olson, Jody C.; Ott, Melissa; Sangha, Harbaksh; Vasquez, Donald G.; Whitt, Stevan P.; Wilkins, Harry E.; Moncure, Michael
Abstract : Objectives: To evaluate the improvement in lung donation and immediate lung function after the implementation of a 360° rotational positioning protocol within an organ procurement organization in the Midwest. Design: Retrospective observational study. Setting: The Midwest Transplant Network from 2005 to 2017. Rotational positioning of donors began in 2008. Subjects: Potential deceased lung donors. Interventions: A 360° rotational protocol. Presence of immediate lung function in recipients, change in PaO2 :FIO2 ratio during donor management, initial and final PaO2 :FIO2 ratio, and proportion of lungs donated were measured. Outcomes were compared between rotated and nonrotated donors. Measurements and Main Results: A total of 693 donors were analyzed. The proportion of lung donations increased by 10%. The difference between initial PaO2 :FIO2 ratio and final PaO2 :FIO2 ratio was significantly different between rotated and nonrotated donors (36 ± 116 vs 104 ± 148; p < 0.001). Lungs transplanted from rotated donors had better immediate function than those from nonrotated donors (99.5% vs 68%; p < 0.001). Conclusions: There was a statistically significant increase in lung donations after implementing rotational positioning of deceased donors. Rotational positioning significantly increased the average difference in PaO2 :FIO2 ratios. There was also superior lung function in the rotated group. The authors recommend that organ procurement organizations consider adopting a rotational positioning protocol for donors to increase the lungs available for transplantation. Abstract : Supplemental Digital Content is available in the text.